WebGL tower defense game with implementation of A* intelligence technique - Kang, Cheng Yong (2014)
This reseach focused on intelligent strategy game named Tower Defense which allow good interaction between players and the game. In this 10 levels of game, players are allowed to build and arrange towers in order to attract the enemy (fruits). This game was develop using JavaScript Object in webGL platform which PNG was used as the source of images. A-Star intelligence technique been implemented to assist the enemy in finding the shortest path from the starting point to the end point of game. This intelligent strategy game may increase the attraction of players toward this game.